Co-immunoprecipitation based isolation and identification of Interacting Phytal and Rheumatoid arthritis subject’s serum globulins proteins - Chunduri, Jayaprada; Bhatt, Pragati; Desai, Rupal H (Journal of BioScience and Biotechnology, 2024)
Phytalproteins have an immense role in plant’s growth and sustenance processes. They can be used as nutritional enhancers of foods we consume. Rheumatoid arthritis is an autoimmune disorder, prevalent in both sexes of humans and especially those above 50 years. Ayurveda suggests plant oils to reduce the pain and inflammation caused by Rheumatoid arthritis (RA). The current study is based on immunoprecipitation interactions between phytal proteins and gamma globulins of Rheumatoid arthritis subjects to assess their role in diagnostics or as immune modulators. A comparative study of proteins of Murraya koenigi, Basal alba (leaves), and Sapindus mukorossi (seed) has been considered for immunoassays. The protein-protein binding capability assessment has shown a positive response with Murraya koenigi phytal proteins than that of Basal alba. The globulins of Sapindus mukorossi seed proteins indicated more specific and prominent interactions than the previous two. The co-immunoprecipitation bands were subjected to LC/MS followed by Bioinformatic studies based on meta Hawkdock and PDB sum. Based on the docking study’s scores, hydrogen bonds and salt bridges, bonding capability between 10 selected gamma globulin proteins and unique proteins, and 4 phytal proteins of Indian soapberry were established. Q3KNS1(sperm function), unique protein Q7Z351(associated with the immune system) and A0A024617 (Alpha-1-antitrypsin) proteins of human serum showed an interaction with A0A0U1XK40, A0A7H1CQR4 of Sapindicus. Studies of RuBISCo (A0A0U1XK40) of Indian soap nut protein and Q3KNS1(Patched domain-containing protein 3 that controls sperm development or sperm function and affects Rheumatoidism of muscles) interactions, can be considered for further studies.